Geometric calibration of markerless optical surgical navigation system. Issue 2 (16th January 2019) - Lin, Qinyong; Cai, Ken; Yang, Rongqian; Xiao, Weihu; Huang, Jinhua; Zhan, Yinwei; Zhuang, Jian
Abstract: Background: Patient‐to‐image registration is required for image‐guided surgical navigation, but marker‐based registration is time consuming and is subject to manual error. Markerless registration is an alternative solution to avoid these issues. Methods: This study designs a calibration board and proposes a geometric calibration method to calibrate the near‐infrared tracking and structured light components of the proposed optical surgical navigation system simultaneously. Results: A planar board and a cylinder are used to evaluate the accuracy of calibration. The mean error for the board experiment is 0.035 mm, and the diameter error for the cylinder experiment is 0.119 mm. A calibration board is reconstructed to evaluate the accuracy of the calibration, and the measured mean error is 0.012 mm. A head phantom is reconstructed and tracked by the proposed optical surgical navigation system. The tracking error is less than 0.3 mm. Conclusions: Experimental results show that the proposed method obtains high accessibility and accuracy and satisfies application requirements.